Arthurian literature. - Archibald, Elizabeth, 1951-; Johnson, David F. (David Frame), 1956- (D.S. Brewer, 2015)
The essays collected here put considerable emphasis on Arthurian narratives in material culture and historical context, as well as on purely literary analysis, a reminder of the enormous range of interests in Arthurian narratives in the Middle Ages, in a number of different contexts. The volume opens with a study of torture in texts from Chrétien to Malory, and on English law and attitudes inparticular. Several contributors discuss the undeservedly neglected Stanzaic Morte Arthur, a key source for Malory. His Morte Darthur is the focus of several essays, respectively on thesources of the "Tale of Sir Gareth"; battle scenes and the importance of chivalric kingship; Cicero's De amicitia and the mixed blessings and dangers of fellowship; and comparison of concluding formulae in the Winchester Manuscript and Caxton's edition. Seven tantalizing fragments of needlework, all depicting Tristan, are discussed in terms of the heraldic devices they include. The volume ends with an update on newly discovered manuscripts of Geoffrey of Monmouth's seminal Historia regum Britanniae, the twelfth-century best-seller which launched Arthur's literary career. Elizabeth Archibald is Professor of English Studies at Durham University, and Principal of St Cuthbert's Society; David F. Johnson is Professor of English at Florida State University, Tallahassee. Contibutors: David Eugene Clark, Marco Nievergelt, Ralph Norris, Sarah Randles, Lisa Robeson, Richard Sévère, Jaakko Tahkokallio, Larissa Tracy.